2018
DOI: 10.1159/000492162
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>Staphylococcus epidermidis</i></b> Activates Aryl Hydrocarbon Receptor Signaling in Human Keratinocytes: Implications for Cutaneous Defense

Abstract: Bacterial challenge of keratinocytes with the abundant skin commensal Staphylococcus epidermidis induces distinct innate immune responses, but the underlying molecular mechanisms are still emerging. We report that the aryl hydrocarbon receptor (AhR) was activated in human primary keratinocytes infected with S. epidermidis, leading to induction of the AhR-responsive gene cytochrome P450 1A1 (CYP1A1). In addition, functional AhR was required for S. epidermidis-mediated induction of IL-1β expression in keratinocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 44 publications
5
35
0
Order By: Relevance
“…The effects observed in our colonised models are less acute and rather in line with what is seen for commensal communities in vivo. For example, similar to what is seen in host–microbiome animal studies both organisms lead to increased gene expression of β-defensins DEFB3A and DEFB4A (Lai et al 2010 ; Rademacher et al 2019 ). These β-defensins are critical but not exclusive for host defence, with induction of DEFB3A relying, amongst other things, on activation of TLR2 (Shin and Choi 2010 ).…”
Section: Discussionmentioning
confidence: 72%
“…The effects observed in our colonised models are less acute and rather in line with what is seen for commensal communities in vivo. For example, similar to what is seen in host–microbiome animal studies both organisms lead to increased gene expression of β-defensins DEFB3A and DEFB4A (Lai et al 2010 ; Rademacher et al 2019 ). These β-defensins are critical but not exclusive for host defence, with induction of DEFB3A relying, amongst other things, on activation of TLR2 (Shin and Choi 2010 ).…”
Section: Discussionmentioning
confidence: 72%
“… higher yeast counts have been found to correlate with SD symptom and/or severity; M furfur (formerly known as Pityrosporum orbiculare , P ovale , P furfur ) has been implicated as the most common source of dandruff; Malassezia was shown to activate the NLRP3 inflammasome via the dectin‐1 and Syk signalling cascade, causing the release of the proinflammatory cytokine IL‐1β, and altered host cytokine expression profile; of the diverse chemical entities that are effective in treating SD and dandruff—such as azoles, hydroxypyridones, allylamines, selenium and zinc pyrithione—the main shared mechanism of action is their antifungal activity; Malassezia utilizes human sebum triglycerides as food, and the metabolites such as oleic acid and arachidonic acid cause aberrant epidermal differentiation, barrier defects, and inflammatory response; Malassezia infection has also been reported in domestic animals such as goats, cats and dogs as well as monkeys, associated with seborrhoea (dry or greasy) and dermatitis, suggesting that mammalian skin shares an evolutionarily conserved hyperresponsiveness to this yeast; Malassezia can produce metabolites such as indirubin and indolo[3,2‐b]carbazole that stimulate the aryl hydrocarbon receptor and can thereby modulate antigen presenting cell functions, at least in vitro . Given that aryl hydrocarbon receptor‐mediated signalling is increasingly appreciated as a major player in human skin physiology and pathology that modulates, for example skin responses to environmental toxins and bacterial stimuli, this potential pathway through which the yeast might impact on skin inflammation deserves more systemic dissection. …”
Section: Sd Aetiology: Malassezia Yeast—cause or Associated Factor?mentioning
confidence: 99%
“…Moreover, overexpression of constitutively activated AHR in basal epidermal KCs in mice led to AD-like inflammation [116,117]. Recently, it was shown that Staphylococcus epidermidis is able to trigger IL-1β and IL-1α in an AHR-dependent manner in HSEs, suggesting a pro-inflammatory role of AHR [118]. This proves the complexity of the mechanism of action of such transcription factors.…”
Section: 3d Cultures Helped Unravel New Pathogenic Pathways In Atomentioning
confidence: 99%